The Optical Diode Ideality Factor Enables Fast Screening of Semiconductors for Solar Cells. Issue 12 (30th October 2018) - Babbe, Finn; Choubrac, Leo; Siebentritt, Susanne
Abstract : In the search for new materials for solar cells, a fast feedback is needed. Radiative efficiency measurements based on photoluminescence (PL) are the tool of choice to screen the voltage a material is capable of. Additionally the dependence of the radiative efficiency on excitation density contains information on the diode ideality factor, which determines in turn the fill factor of the solar cell. Both parameters are immediate ingredients of the efficiency of a solar cell and can be determined from PL measurements, which allow fast feedback. The method to determine the optical diode ideality factor from PL measurements and compare to electrical measurements in finished solar cells are discussed. Abstract : A method for the determination of an optical diode factor for bare absorbers is derived and verified experimentally. By combining this with quasi Fermi level splitting measurements, it is possible to predict the VOC and FF of a solar cell before device finishing. Comparing the optical diode factor to the diode factor of devices allows one to unveil limitations by interfaces.